Description and process evaluation of pharmacists' interventions in a pharmacist-led information technology-enabled multicentre cluster randomised controlled trial for reducing medication errors in general practice (PINCER trial) - Howard, Rachel; Rodgers, Sarah; Avery, Anthony; Sheikh, Aziz (Wiley, 2014)
Objective